Digital acoustic analysis of five vowels in maxillectomy patients - Sumita, Y. I.; Ozawa, S.; Mukohyama, H.; Ueno, T.; Ohyama, T.; Taniguchi, H. (Journal of oral rehabilitation, 2002)
The aim of the study was to characterize the acoustics of vowel articulation in maxillectomy patients. Digital acoustic analysis of five vowels, /a/, /e/, /i/, /o/ and /u/, was performed on 12 male maxillectomy patients and 12 normal male individuals. A simple set of acoustic descriptions called the first and second formant frequencies, F1 and F2, were employed and calculated based on linear predictive coding. The maxillectomy patients had a significantly lower F2 for all five vowels and a significantly higher F1 for only /i/ vowel. From the data plotted on an F1–F2 plane in each subject, we determined the F1 range and the F2 range, which are the differences between the minimum and the maximum frequencies among the five vowels. The maxillectomy patients had a significantly narrower F2 range than the normal controls. In contrast, there was no significant difference in the F1 range. These results suggest that the maxillectomy patients had difficulty in controlling F2 properly. In addition, the speech intelligibility (SI) test was performed to verify the results of this new frequency range method. A high correlation between the F2 range and the score of SI test was demonstrated, suggesting that the F2 range is effective in evaluating the speech ability of maxillectomy patients.